Potential of human fetal chorionic stem cells for the treatment of osteogenesis imperfecta. - Jones, G; Moschidou, D; Abdulrazzak, H; Kalirai, B; Vanleene, M; Osatis, S; Shefelbine, S; Horwood, N; Marenzana, M; De Coppi, P; Bassett, J; Williams, G; et al. (2014)
Osteogenesis imperfecta (OI) is a genetic bone pathology with prenatal onset, characterized by brittle bones in response to abnormal collagen composition. There is presently no cure for OI. We previously showed that human first trimester fetal blood mesenchymal stem cells (MSCs) transplanted into a murine OI model (oim mice) improved the phenotype. However, the clinical use of fetal MSC is constrained by their limited number and low availability. In contrast, human fetal early chorionic stem cells (e-CSC) can be used without ethical restrictions and isolated in high numbers from the placenta during ongoing pregnancy. Here, we show that intraperitoneal injection of e-CSC in oim neonates reduced fractures, increased bone ductility and bone volume (BV), increased the numbers of hypertrophic chondrocytes, and upregulated endogenous genes involved in endochondral and intramembranous ossification. Exogenous cells preferentially homed to long bone epiphyses, expressed osteoblast genes, and produced collagen COL1A2. Together, our data suggest that exogenous cells decrease bone brittleness and BV by directly differentiating to osteoblasts and indirectly stimulating host chondrogenesis and osteogenesis. In conclusion, the placenta is a practical source of stem cells for the treatment of OI.